Stablecoins as a crypto safe haven? Not all of them! - Eduard Baumöhl; Tomas Vyrost (ZBW – Leibniz Information Centre for Economics, 2020)
We test the safe haven properties of the largest stablecoins (USDT, USDC, TUSD, PAX, DAI, GUSD) against the standard “nonstable” coins (BTC, ETH, XRP, BCH, LTC). Our dataset comprises high-frequency 1-minute data calculated as volume-weighted averages across 18 exchanges where these cryptocurrencies are traded, thus capturing the entire price movement around the world. Using a quantile coherency cross-spectral measure, we find that only TUSD, PAX, and GUSD can serve as safe havens.
Keywords: G11; G15; F31; 330; cryptocurrencies; stablecoins; quantile dependence; cross-spectral analysis; diversification; safe haven